2012
DOI: 10.7744/cnujas.2012.39.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of wild grape (Vitis coignetiae) on the quality of egg

Abstract: : This study was conducted to investigate the effect of dietary supplementation of wild grape (Vitis coignetiae) on egg qualities. Laying hens were randomly assigned to three different dietary groups containing 0, 0.25, and 0.5% of wild grape and fed for 8 weeks, respectively. Eggs were collected after feeding period and stored at 4℃ for 7 days. Egg quality traits and cholesterol level of egg yolk were measured at 0 and 7 days of storage. There were no significant differences in total cholesterol content of eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Won (2009) reported that wild grape juice increased the antioxidative activity of the blood and liver of rats that were fed high oxidized lipids. Furthermore, Yong et al (2012) recently reported an improvement in the quality and freshness of eggs from layers that were fed wild grape powder.…”
Section: Introductionmentioning
confidence: 99%
“…Won (2009) reported that wild grape juice increased the antioxidative activity of the blood and liver of rats that were fed high oxidized lipids. Furthermore, Yong et al (2012) recently reported an improvement in the quality and freshness of eggs from layers that were fed wild grape powder.…”
Section: Introductionmentioning
confidence: 99%